Bochkarev Inequality for the Fourier Transform of Functions in the Lorentz Spaces \( L_2,r(R) \) - Mussabayeva, G.K.; Tleukhanova, N.T. (Eurasian Mathematical Journal, 2015)
In this article we prove an analogue of Hardy–Littlewood–Stein inequality for the Fourier transform in Lorentz space \( L_2,r(R) \).